2018
DOI: 10.3390/ijms19061664
|View full text |Cite
|
Sign up to set email alerts
|

Luteoloside Inhibits Proliferation and Promotes Intrinsic and Extrinsic Pathway-Mediated Apoptosis Involving MAPK and mTOR Signaling Pathways in Human Cervical Cancer Cells

Abstract: Cervical cancer is a common gynecological malignancy with high incidence and mortality. Drugs commonly used in chemotherapy are often accompanied by strong side-effects. To find an anti-cervical cancer drug with high effects and low toxicity, luteoloside was used to treat the cervical cancer cell line Hela to investigate its effects on cell morphology, proliferation, apoptosis, and related proteins. The study demonstrated that luteoloside could inhibit proliferation remarkably; promote apoptosis and cytochrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 58 publications
5
27
1
Order By: Relevance
“…Recently, evidence indicated that TNALP could regulate cranial base growth and synchondrosis maturation via mitogen-activated protein kinase (MAPK) signalling (24). Previous studies have also indicated the role of MAPK signaling in tumorigenesis (2528), and demonstrated that oncogenes promote tumor growth and metastasis through the MAPK signaling pathway (29). Ectopic activation of the MAPK signaling pathway enhances the progression of cancer (30).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, evidence indicated that TNALP could regulate cranial base growth and synchondrosis maturation via mitogen-activated protein kinase (MAPK) signalling (24). Previous studies have also indicated the role of MAPK signaling in tumorigenesis (2528), and demonstrated that oncogenes promote tumor growth and metastasis through the MAPK signaling pathway (29). Ectopic activation of the MAPK signaling pathway enhances the progression of cancer (30).…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have found that luteoloside and celecoxib both have COX-2-independent effects on the signal pathways, such as MAPK/p38, and ERK. (Wu et al, 2004;Hua et al, 2005;Ha et al, 2006;Kadam et al, 2007;Park et al, 2010;Wang et al, 2013;Akram et al, 2015;Jeon et al, 2015;Li et al, 2019;Shao et al, 2018). Although these results have not been applied to studies about analgesic effects, these mechanisms may be the reason of the synergistic effect in the acute analgesic role due to the critical role of MAPK/p38 and ERK signal pathways in the pain regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, recent studies found Glossogyne tenuifolia extract attenuates inflammatory mediator synthesis partly through down-regulating NF-κB activation ( Wu et al., 2004 ; Ha et al., 2006 ). What is more, luteoloside can inhibit cell proliferation via mitogen-activated protein kinase (MAPK) and mammalian target of rapamycin (mTOR) signaling pathways ( Shao et al., 2018 ). The anti-inflammatory effect of luteoloside and its effects on pain-related signaling pathways indicate its application prospect in chronic inflammatory pain.…”
Section: Introductionmentioning
confidence: 99%
“…Luteolin is a type of flavonoid that inhibits proliferation involving MAPK and mTOR signalling pathways in various tumour cell lines [41].…”
Section: Classification Of Flavonoids and Other Polyphenolic Compomentioning
confidence: 99%